ANALYSIS THE EFFECT OF SURFACE HARDENING TEMPERATURES TO HARDEN THE AISI 1050 GEARS TEETH - Raka Pradewa - Nim: 13714038 , Mahestra
AISI 1050 is medium carbon steel that used for gears material. Wear resistance is a mechanical property that must be considered to satisfy service requirements. To increase wear resistance value, can be done by increasing the value of hardness resulting from the microstructure that depends on its heat treatment(s). Chemical composition of the gear has been characterized using OES. The gear heat treatment process has conducted at temperatures of 700, 750, 800, and 900℃ which were all held for 7,5 minutes and then quenched in water. At temperatures of 700℃ and 750℃, microstructure that obtained was globular cementite phase (spheroidite) on α ferrite matrix. At temperatures of 800℃ and 900℃, microstructure that obtained was martensite phase. Hardness value of gear case, for specimen 1 is 194,04 HV, specimen 2 202,94 HV, specimen 3 is 734,6 HV, and specimen 4 is 908 HV with the highest hardness because when the heating temperature increases, austenite grains will be coarser which results in a longer Ã‚Â“needlesÃ‚Â” structure obtained in martensite phase. Hardness value of gear core, for specimen 1 is 193,28 HV, specimen 2 195,68 HV, specimen 3 is 248,8 HV, and specimen 4 is 322 HV.